Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (University of North Carolina Press, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Disponible en livre numérique et en format imprimé.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

L'Histoire des femmes au Québec depuis quatre siècles - Collectif Clio. (Le Jour, 1992)
Dans une version revue et mise à jour de l'édition de 1982 (Quinze), cet ouvrage repère, du début du xviie siècle à nos jours, les changements qui ont affecté les Québécoises ainsi que les phénomènes qui ont marqué un point tournant dans la transformation de leur image et de leur rôle au sein de notre société. Des figures anonymes – paysannes, autochtones, immigrantes, etc. – à celles qui ont occupé le devant de la scène, toutes les femmes qui ont redéfini le paysage féminin y ont droit de cité.
Keywords: 1600-1699; amériques; cours; cycles supérieurs; fem1000; fem7000; his4550; histoire des femmes*; histoire et politique; lit3220; lit3495; mouvements féministes; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Les femmes autochtones et la justice pénale - Jaccoud, Mylène (Criminologie, 1992)
The interest in understanding and analyzing the situation of native women within the penal process is recent and seems to be limited by the inordinate attention paid by researchers to the overrepresentation of native women. This article is an account of the findings and analyses made to date in this recent sector of research. It presents an inventory of the principal data concerning the confrontation of native women with the penal process. It proposes a synthesis of the principal analyses of the problems of native women with the system of justice by presenting a critical analysis of the socio-structural model of LaPrairie.
Keywords: amériques; approches et analyses; canada; cours; criminologie; discipline; droit; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; racisme; régions géographiques; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Indigena: perspectives autochtones contemporaines - McMaster, Gerald R.; Martin, Lee-Ann; Bérubé, Christian; Canadian Museum of Civilization (Musée canadien des civilisations, 1992)
Publié à l'occasion du 500e anniversaire de la découverte de l'Amérique, ce catalogue regroupe des essais et des textes d'artistes et une documentation des travaux de 19 artistes afin de dénoncer le caractère eurocentrique des célébrations. Alors que Webster et Ippellie revoient les effets de la colonisation sur le patrimoine amérindien et sur celui des peuples de l'Arctique, Wendayete examine la logique matérialiste de l'historiographie canadienne non-autochtone et l'oppose à un concept d'américité philosophique. Todd et Young Man s'attaquent respectivement aux notions de postmodernisme et de ghettoïsation en art. Comprend des textes d'artistes.
Traduction de: Indigena, contemporary native perspectives.
Keywords: amériques; approches et analyses; canada; cours; féminisme autochtone; har4610; histoire et politique; premier cycle; régions géographiques; thématiques

The persistent desire: A femme-butch reader - Nestle, Joan (Alyson publ, 1992)
Dans cette anthologie « canonique » des identités Butch-Femme, Joan Nestle retrace 200 ans d'histoire lesbienne, des lettres aux mémoires en passant par les nouvelles. Nestlé passe en revue une décennie de tentatives visant à reconstruire et à comprendre le sens et la valeur des relations butch-femme pour la lesbienne contemporaine, en s'appuyant sur l'histoire orale, la fiction, la poésie et le fantastique.
https://transreads.org/wp-content/uploads/2021/07/2021-07-18_60f48dbbdb063_ThePersistentDesireaFemme-ButchReaderbyJoanNestlez-lib.org_.pdf
Keywords: amériques; anthologie; arts; butch/femme; discipline; désir; histoire et politique; littérature; personnes lesbiennes; poésie; ressource en ligne; régions géographiques; sexualité; thématiques; états-unis; études littéraires